Partial Frontier Efficiency Analysis - Tauchmann, Harald (Stata Journal, 2012)
Despite their frequent use in applied work, nonparametric approaches to efficiency analysis-namely, data envelopment analysis and free disposal hull- have bad reputations among econometricians. This is mainly because data envelopment analysis and free disposal hull represent deterministic approaches that are highly sensitive to outliers and measurement errors. However, so-called partial frontier approaches have recently been developed, namely, order-m and order-α. These approaches generalize free disposal hull by allowing for superefficient observations to be located beyond the estimated production-possibility frontier. Although these methods are also purely nonparametric, the sensitivity to outliers is substantially reduced by partial frontier approaches enveloping just a subsample of observations. In this article, I introduce the new Stata commands orderm and orderalpha, which implement order-m, order-α, and free disposal hull efficiency analysis in Stata. The commands allow for several options, such as statistical inference based on subsampling bootstrapping. © 2012 StataCorp LP.
WiSo-Import:2015-03-26:5032
Keywords: Decision-making unit; Efficiency; Free disposal hull; Nonparametric; Orderalpha; Orderm; Outlier-robust; Partial frontier; st0270